2011
DOI: 10.1002/jbm.a.33285
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of the lysine in the gamma chain dodecapeptide of human fibrinogen is not enhanced by adsorption to poly(ethylene terephthalate) as measured by biotinylation and mass spectrometry

Abstract: Conformational changes in adsorbed fibrinogen may enhance the exposure of platelet adhesive sites that are inaccessible in solution. To test this hypothesis, mass spectrometric methods were developed to quantify chemical modification of lysine residues following adsorption of fibrinogen to biomaterials. The quantitative method used an internal standard consisting of isotope-labeled fibrinogen secreted by human HepG2 cells in culture. Lysine residues in the internal standard were partially reacted with NHS-biot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…51 Although, the applicability of this technique on adsorbed protein has been previously investigated by many groups, its use has been restricted to determining the labeling profile of just one type of amino acid because of problems related to differences in MS intensities that result from each of the different labeling processes. [27][28][29][30] However, the labeling profile for a single amino acid type provides very limited information for the assessment of the orientation and conformational changes of an adsorbed protein. Therefore, to provide more complete coverage for a given protein, our group recently developed methodology to combine labeling results from multiple target amino acid types applied to a single protein.…”
Section: Quantification Of Secondary Structurementioning
confidence: 99%
See 2 more Smart Citations
“…51 Although, the applicability of this technique on adsorbed protein has been previously investigated by many groups, its use has been restricted to determining the labeling profile of just one type of amino acid because of problems related to differences in MS intensities that result from each of the different labeling processes. [27][28][29][30] However, the labeling profile for a single amino acid type provides very limited information for the assessment of the orientation and conformational changes of an adsorbed protein. Therefore, to provide more complete coverage for a given protein, our group recently developed methodology to combine labeling results from multiple target amino acid types applied to a single protein.…”
Section: Quantification Of Secondary Structurementioning
confidence: 99%
“…15,17 Some of the methods that can provide information on adsorbed protein orientation and tertiary (and quaternary) structure include fluorescence, [18][19][20][21] time-of-flight secondary-ion mass spectrometry, [22][23][24] nuclear magnetic resonance spectroscopy (NMR), 25,26 and amino acid labeling/mass spectrometry (AAL/MS). [27][28][29][30][31] Methods for the determination of secondary structure of adsorbed proteins include Fourier transform infrared spectroscopy, 32,33 surface enhanced Raman scattering, 34,35 and circular dichroism spectropolarimetry (CD). 27,[36][37][38][39] Unfortunately, as the size of the protein increases, many of the spectral signatures that are needed for tertiary structure determination using fluorescence and NMR overlap, introducing much subjectivity into the analyses, thus making it difficult to accurately interpret the configuration of the adsorbed protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of different material surfaces and adsorption conditions on the structure and enzymatic activity of adsorbed RNase A is not very well understood. Previous studies on the adsorption behavior of proteins have shown that the adsorbed orientation and adsorption-induced changes in protein conformation and enzymatic activity are a result of the combination of a protein’s internal stability relative to the ability of protein–surface and protein–protein interactions (PPI) on the surface to perturb the protein’s structure. Although many previous studies have been published that relate adsorption-induced loss in protein structure to loss of bioactivity, most of these studies were done using techniques like circular dichroism spectropolarimetry (CD), which, though useful, are only scalar indicators of the molecular processes underlying the involved processes. , Alternatively, techniques like amino acid labeling and mass spectrometry (AAL/MS), though localized, can be used to identify the shifts in the solvent exposure of the residues within the tertiary structure of adsorbed protein. ,, Additionally, these types of techniques are especially relevant in applications that require molecular-scale understanding of the processes underlying the loss in the bioactivity of a protein, despite retaining its near-native secondary structure …”
Section: Introductionmentioning
confidence: 99%